High-intensity training versus traditional exercise interventions for promoting health - Nybo, L.; Sundstrup, E.; Jakobsen, M. D.; Mohr, M.; Hornstrup, T.; Simonsen, L.; Bülow, J.; Randers, M. B.; Nielsen, J. J.; Aagaard, P.; Krustrup, P. (Medicine & Science in Sports & Exercise, 2010)
Purpose: The purpose of this study was to determine the effectiveness of brief intense interval training as exercise intervention for promoting health and to evaluate potential benefits about common interventions, that is, prolonged exercise and strength training.